Research Trends in Halal Certification and Labeling: Bibliometric Analysis and Systematic Literature Review - Azis, Saipul; Hulwati, Hulwati; Duhriah, Duhriah; Novia, Aidil (Abdurrauf Journal of Islamic Studies, 2024)
Indonesia as a country with a Muslim majority makes halal not only a religious principle, but also a significant economic driver. Halal products are no longer just a preference, but a necessity for the majority of consumers in Indonesia. This study aims to see the research trend on halal certification and labeling with bibliometric analysis and systematic literature review. This type of research uses a combined qualitative and quantitative approach in the form of bibliometric analysis, as well as a systematic literature review (SLR) related to halal certification and labeling. Quantitative and qualitative approaches are used using Google Scholar data with a time span of 2015-2023 with the keywords "sertifikasi dan labelisasi halal ". From the bibliometric analysis, there is a publication trend from year to year where the publication trend of research on halal certification and labeling during the period 2018-2023 illustrates a significant increase in terms of the number of publications where in 2023 it was the year with the highest number of publications with 67 article publications, then the Indonesian Journal of Hala became the top journal that published a lot of halal certification and labeling. then the emergence of keywords that appear in several publications, namely "Halal Certification" and "Halal Label". Then from the Vosviewr data processing, 4 clusters were produced which produced several sub-themes including the importance of halal labeling, the importance of halal certification, the role of BPJPH in halal certification and labeling and the importance of awareness of halal products. [Indonesia sebagai negara dengan mayoritas beragama islam menjadikan halal bukan hanya sekadar prinsip agama, tetapi juga telah menjadi pendorong ekonomi yang signifikan. Produk halal bukan lagi sekadar preferensi, tetapi keharusan bagi mayoritas konsumen di Indonesia. Penelitian ini bertujuan untuk melihat tren penelitian tentang sertifikasi dan labelisasi halal dengan analisis bibliometrik dan systematic literature review. Jenis penelitian ini menggunakan pendekatan gabungan kualitatif dan kuantitatif berupa analisis bibliometrik, serta systematic literature review (SLR) terkait seertifikasi dan labelisasi halal. Pendekatan kuantitatif dan kualitatif digunakan menggunakan data Google Scholar dengan rentang waktu 2015-2023 dengan kata kunci”sertifikasi dan labelisasi halal”. Dari analisis bibliometrik terdapat tren publikasi dari tahun ketahun dimana pada tren publikasi penelitian mengenai sertifikasi dan labelisasi halal selama periode 2018-2023 menggambarkan sebuah peningkatan yang signifikan dari segi jumlah publikasi dimana ditahun 2023 menjadi tahun dengan jumlah publikasi tertinggi dengan 67 publikasi artikel, selanjut jurnal Indonesia Journal of Hala menjadi top jurnal yang banyak mempublikasi sertifikasi dan labelisasi halal. kemudian kemunculan kata kunci yang muncul dibeberapa publikasi yakni "Halal Certification" dan "Halal Label”. Kemudian dari olah data Vosviewr menghasilkan 4 kluster yang menghasilkan beberapa subtema diantaranya pentingnya labelisasi halal, pentingnya sertifikasi halal, peran BPJPH dalam sertifikasi dan Labelisasi halal dan pentingnya Kesadaran pada produk halal].